2017
DOI: 10.1039/c6tc05551f
|View full text |Cite
|
Sign up to set email alerts
|

Stable N-heterocyclic carbene (NHC) cyclometalated (C^C) gold(iii) complexes as blue–blue green phosphorescence emitters

Abstract: Blue and blue-green phosphorescent Au(iii) compounds based on a novel C^C chelate ligand framework are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Emission quantum yields F in dichloromethane solution at room temperature range between 3a nd 10 %b eing higher than the yields of many (C^N^C) analogues. [10] Obviously,t he quantum yields are not affected by the lateral donor of the pincer,b ut the ligand besides the pincer: The C 6 F 5 substituted systems 39 and 40 phosphoresce up to three times more efficient than the PhCC analogues 34 and 35.T his is especially noteworthy,s ince the opposite finding was reported by Venkatesan and co-workers aboutt he luminescence of cyclometalated [(C^N)Au III ] [64] and [(C^C')Au III ] [29] complexes. The authors found higher emission quantum yields for phenylethinyl substitutedc omplexes than for pentafluorophenyl substituted ones.…”
Section: Absorption and Emission Propertiesmentioning
confidence: 83%
See 2 more Smart Citations
“…Emission quantum yields F in dichloromethane solution at room temperature range between 3a nd 10 %b eing higher than the yields of many (C^N^C) analogues. [10] Obviously,t he quantum yields are not affected by the lateral donor of the pincer,b ut the ligand besides the pincer: The C 6 F 5 substituted systems 39 and 40 phosphoresce up to three times more efficient than the PhCC analogues 34 and 35.T his is especially noteworthy,s ince the opposite finding was reported by Venkatesan and co-workers aboutt he luminescence of cyclometalated [(C^N)Au III ] [64] and [(C^C')Au III ] [29] complexes. The authors found higher emission quantum yields for phenylethinyl substitutedc omplexes than for pentafluorophenyl substituted ones.…”
Section: Absorption and Emission Propertiesmentioning
confidence: 83%
“…The emission spectra resemble the ones of other [(C^C^N)Au III ] [23] and [(C^N^C)Au III ]c omplexes [10,16] as well as biphenyl-based [(C^C)Au III ] [63] or cyclometalated pyridine [64] and carbene [(C^C')Au III ]c omplexes. [29] Thus, the p orbitalo ft he emissive p!p* 3 IL state is almost exclusively centred at the (bi)phenyl unit of the respective pincer ligand.…”
Section: Absorption and Emission Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[42,43] We anticipated that the donor properties of the triazolylidene moiety would benefit the emission efficiencies of cyclometalatedP t IV complexes by increasing the energy of deactivating excited states of LMCT character to ag reater extent than in the case of 2-arylpyridines. Cyclometalating aryl-NHC ligands have previously been employed for the synthesis of luminescentc omplexes of Ir III , [44][45][46][47][48][49][50][51][52] Pt II , [53][54][55][56] and Au III [57] with enhanced emission properties, often as non-chromophorics upporting ligands. However, most of them are normal 2-imidazolylidene-typea ryl-NHCs, whereas mesoionic aryl-NHCs have only been employed to prepare a limited number of luminescent Pt II complexeso ft he type [Pt(C^C*)(O^O)] (O^O = b-diketonate).…”
Section: Introductionmentioning
confidence: 99%
“…Organogold(III) complexes with emission color towards the blue spectral region have been reported in the literature; for instance, in 2017, Venkatesan and co-workers reported gold(III) complexes constructed with NHC-containing C^C chelates that show vibronic-structured emission with maxima locating at~380-480 nm. [4] Yam and co-workersa lso reported blue gold(III) phosphors with photoluminescence maxima at~470-500 nm ande lectroluminescencem aximaa t~480-500nm. [1k-l, 5] However,v ibronically structured 3 IL excited states of gold(III) complexes have long emissionl ifetimes( tens to hundreds of microseconds), thus rendering these complexes unsuitablef or the fabrication of OLEDsw ithp ractical interest.…”
Section: Introductionmentioning
confidence: 99%